Citizenship, capabilities and arts in Unidad educativa Fe y Alegría "San Francisco", Barquisimeto, Lara State (Mayéutica Revista Científica de Humanidades y Artes, 2020)
Human Development takes into account various dimensions to expand access to opportunities for a higher quality of life. One of the aspects thatcontributes to the existence of processes oriented towards this particular approach is citizenship, because it allows people to exercise their rights and duties, possess a collective identity and maintain a behaviour based on civic values. The objective of this research was to understand the formative processes of the Fe y Alegría School "San Francisco" Educational Unit of the projects that use art as a tool for the construction of citizenship, considering its relationship with the central capacities and Human Development. From the qualitative modality, methodological strategies typical of hermeneutics were used: reading of documents, indepth interviews and group interviews.Among the findings are that educational projects that use the arts as a tool for the cultivation and strengthening of citizenship can generate a positive impact, thanks to the set of skills and training in values that lead to a community to promote changes that allow them to achieve a better quality of life.
Keywords: citizenship; education; human development; central capabilities; arts